COVID-19 health literacy of adults in the Philippines - Gatdula, Joshua L.
Ninety-respondents from the National Capital Region were gathered to answer the COVID-19 health literacy survey. Data was gathered during the COVID-19 pandemic in the Philippines (July to August 2021). The COVID-19 health literacy level of the respondents was assessed using the HLS-COVID-Q22 tool. The tool was answered on a four-point scale ranging from 1 (very difficult) to 4 (very easy). Mean scores on the test were based on the scoring method, ranging from 1 to 4.